4(k+-10)+3k=k+9

Simple and best practice solution for 4(k+-10)+3k=k+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(k+-10)+3k=k+9 equation:



4(k+-10)+3k=k+9
We move all terms to the left:
4(k+-10)+3k-(k+9)=0
We add all the numbers together, and all the variables
4(k-10)+3k-(k+9)=0
We add all the numbers together, and all the variables
3k+4(k-10)-(k+9)=0
We multiply parentheses
3k+4k-(k+9)-40=0
We get rid of parentheses
3k+4k-k-9-40=0
We add all the numbers together, and all the variables
6k-49=0
We move all terms containing k to the left, all other terms to the right
6k=49
k=49/6
k=8+1/6

See similar equations:

| 3x+5(3x-5)=30 | | 180=96+12x-23 | | 180=96+12x+19 | | 9x^2+4x-2=14 | | x+2x=1525 | | 8=m-79/2 | | 2x-1/2-x50+15=90 | | 2x-1/2x50+15=90 | | 12(18x+28)–3x=26 | | –4w=6−3w | | 12^x-5=9 | | 180=96+5y+19 | | 15(p+-5)+3p=p+81 | | 12^x-9=9 | | c−515=5 | | 4(k+-8)+6k=k+9 | | 4(k+-12)+6k=k+9 | | 90=5x(2x-30) | | 6x+1=2x+14 | | 8t+9=7t | | 142=10x+12 | | 8p+2=-10 | | 4(t−65)=64 | | 180=96+12x+19+12x-23 | | 3(a-5)+14a=a+9 | | 140=11x+19 | | (5x+21)=(9x-7) | | 19-2k=9 | | 7+5x3x+5=90 | | 200=12x+20 | | 6t^2=-18 | | 5x+73x+5=90 |

Equations solver categories